A comparative study of variants of pegylated interferon alpha in treatment of chronic HCV patients. Issue 6 (23rd April 2015) - El Sabaawy, Dalia; El‐Haggar, Sahar; El‐Bahrawy, Hoda; Waked, Imam; El‐Said, Hala
<x xml:space="preserve">Abstract</x> HCV infection presents a vast burden in the regions of high prevalence such as Egypt, where most HCV isolates are genotype 4b. Combined treatment of three variants of pegylated interferon and ribavirin is still the standard of care in Egypt. However, no conclusive data confirming their efficacy are available. Here, 60 chronic HCV patients were randomized for ribavirin plus Peg Intron (PEG‐IFNα‐2b), Pegasys (PEG‐IFNα‐2a) or Reiveron Retard (PEG‐IFNα‐2a). Serum interferon and antibody (Ab) levels were measured, and responses and costs were compared. Serum interferon levels were higher in Pegasys group (1625.1 ng/mL) followed by Reiveron Retard (1076.5 ng/mL), and Peg Intron group (857.72 ng/mL). Moreover, Ab levels were the lowest in Reiveron Retard group (318.4 ng/mL), followed by Peg Intron (439.93 ng/mL), and Pegasys cases (610.83 ng/mL). The best 24‐week response rates were detected in the Pegasys group (73.3%), followed by Peg Intron (66.67%), and Reiveron Retard (40%). Treatment with both Pegasys and Peg Intron were most cost‐effective. Furthermore, Pegasys was superior in both 6‐month response and serum interferon, despite having higher Ab levels (more antigenicity). Our data have notable clinical implications and suggest that Pegasys may be a superior choice of interferon therapy for chronic HCV under low socioeconomic conditions.